Optimizing outcomes in anal fissure treatment: Indian expert panel consensus on combination strategies - Mital, Kushal; Agarwal, Niranjan (International Journal of Research in Medical Sciences, 2025)
Anal fissures, defined as longitudinal tears in the anoderm, are a common cause of severe anorectal pain, especially during defecation. Despite the availability of both pharmacological and surgical treatments, certain challenges persist in effectively managing chronic anal fissures (CAFs). This manuscript reviews the unmet needs in the management of anal fissures like high recurrence rates, side effects from existing treatments, improper application of topical agents and poor compliance. It also presents the recommendations from an expert panel of surgeons from all over India, aimed at addressing these issues. While standard surgical treatment, such as lateral internal sphincterotomy, is highly effective, it carries the risk of side effects, including fecal incontinence, which can significantly impact quality of life. Consequently, chemical sphincterotomy has emerged as a leading non-invasive approach, with topical agents such as diltiazem and lidocaine serving as key components in the management of anal fissures. The experts recommended the combination of diltiazem and lidocaine for its superior efficacy in promoting healing and reducing anal resting pressure, with fewer side effects than agents like nifedipine and glyceryl trinitrate. This combination offers a promising alternative for patients seeking non-surgical management of anal fissures.